Pier Paolo Pasolini 100 Anos - Marnoto, Rita (2023)
(Coord. Rita Marnoto & Ana Beatriz Andrade) (2023). Pier Paolo Pasolini 100 anos. Coimbra: Secção de Estudos Italianos da Faculdade de Letras da Universidade de Coimbra [140 pp.] [Série Leonardo, 7]. Introdução, 5-6. Textos de Giulio Ferroni, Giovanbattista Tusa, António Pedro Pita, Roberto Gigliucci, Abílio Hernandez, Rita Marnoto, Ana Beatriz Andrade, Giovanni Ricciardi.